The State of Entrepreneurship Education in Public Senior Secondary Schools in Rivers State of Nigeria - Umesi, Chukwudi Dike (International Journal on Integrated Education, 2023)
This research looks at the state of entrepreneurship education in Rivers State's senior secondary public institutions. For this study, two (2) research questions and null hypotheses were developed. The descriptive survey was chosen for the research, and the sample size is 25 people, or 10% of the population overall, with a reliability coefficient of 0.88. The mean score (x), standard deviation (SD), and rank order (RO) statistical techniques were used to examine the study topics, while the t-test was used to test the null hypothesis. According to the study's conclusions, entrepreneurship education has not received enough attention from the Rivers State Government despite the many advantages the program has provided. Based on the data analysis and findings, suggestions were made, including the need for Rivers State public senior high schools to provide an effective education curriculum, as well as a conducive atmosphere and sufficient resources.